Lightweight AR System for Precise Object Geolocation in Real-Time Drone Video - Carvalho, Bruno Eduardo de Oliveira; Luiz Junior, Fabio; Oliveira, Jauvane Cavalcante de; Rosa, Paulo Fernando Ferreira (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
This work presents a lightweight outdoor augmented reality system that enables precise georegistration of virtual objects using video and telemetry from a DJI Mavic 3T drone. The system integrates Real-Time Kinematic (RTK) positioning, multiple strategies for estimating camera orientation, and terrain modeling through a Digital Elevation Model (DEM). An interactive mechanism allows users to instantiate virtual objects by clicking on the video frame, with the ground position computed via 3D ray–DEM intersection. Field tests conducted with the drone flying at altitudes above 100 meters showed a mean positioning error below 5 meters using only the drone-exported orientation. These results highlight the system’s geometric precision under strong projection compression, supporting its use in scenarios such as long-range object annotation, search and rescue coordination, or infrastructure monitoring.